Evaluacion de dos formas de aplicacion del riego sobre el crecimiento y produccion de la berenjena - Gruber, L.=700 1 Lugo, J.G.; Diaz, L.; Bello, M.A.
(Es, En)
Ilus., 11 ref.
Keywords: SOLANUM MELONGENA; RIEGO SUBTERRANEO; CRECIMIENTO; PRODUCCION; VENEZUELA; CINTAS DE RIEGO; BIOAGRO